023 Evaluation of an innovative clinical syllabus to support university curricula. (December 2018) - Porter, L; Simpson, G; Low, B; Tonkin, T; Gowers, N
Abstract : Rationale: Student nurses commonly present in clinical practice displaying difficulty in relating to university taught theory and the impact that has on preserving safety in clinical practice, and how the two correlate. Objectives: The theory and skills syllabus is mapped to university curricula to ensure the link between theory and practice is clearly visible. Methods: A pilot syllabus integrating theory and skills was devised and run in-house at Great Ormond Street Hospital for all pre-registration nurses meaning that the sessions were easily accessible to all. The syllabus design sees a central topic for each week in clinical practice, allowing more students to benefit from extra training and allowing for off-duty patterns enabling us to prioritise the students. It also allows students to attend multiple sessions enabling them to use the theory and apply it to the skill learnt as with repetition and constructive feedback, a skill can be successfully mastered. It is delivered by the multi-disciplinary team from differing specialities and subject areas have been included which are clinically relevant, these sessions are taught using multiple modes of teaching to promote engagement and learning styles. Results: An overall evaluation of the syllabus was conducted using an online survey completed by our student nurses. This yielded 93 results with third-year feedback still to be evaluated. On analysis of this data, the primary results show that 89% of our students found these sessions beneficial for their clinical practice, commenting that this syllabus helps to bridge the theory-practice gap. Feedback received from stakeholders identified the following themes; showing more initiative, problem-solving and increase in confidence and competence being seen enabling them to practice effectively, therefore, promoting professionalism and trust in line with the Nursing and Midwifery Council.